Case Report: Ocular Manifestations and Treatments of Ciliary Body Involvement by Lymphoma - Di, Yu; Ye, Junjie; Han, Ruoan; Li, Mengda; Zhang, Bilei (Frontiers in Oncology, 2021)
Purpose: To describe the ocular clinical features, histopathological findings, and treatment outcomes of lymphomas involving the ciliary body. Methods: We demonstrate three cases of ciliary body involvement by lymphoma from 2013 to 2019 in Peking Union Medical College Hospital (PUMCH). All patients underwent examinations including best corrected visual acuity (BCVA), slit-lamp microscopy, indirect ophthalmoscope, ultrasound biomicroscopy (UBM), and diagnostic vitrectomy. In addition, cytopathology, immunohistochemistry, gene rearrangement, cytometric immunophenotypic, or in-situ hybridization were used for determining the pathological type of lymphoma. Results: The patients were a 25-year-old man, a 52-year-old woman, and a 54-year-old man. Two patients had unilateral involvement, and one patient had bilateral involvement. All patients presented with anterior uveitis and elevated intraocular pressure. Ciliary body masses or infiltration were found in 3 patients. Two patients had diffuse large B-cell lymphoma and one patient had natural killer/T-cell lymphoma. All patients received 0.4 mg methotrexate intravitreal injections, and the ciliary body lesions regressed completely. Conclusion: Lymphomatous involvement of the ciliary body usually presents as an atypical anterior chamber reaction. Vitreous biopsy should be considered in these patients for diagnosis. Methotrexate intravitreal injection combine with chemotherapy or radiotherapy, might extend the survival time and preserve visual acuity for patients with ciliary body involvement by lymphoma.